Response in growth of shallot (Allium ascalonicum L.) to application of mulch and some plant spacing - Irfan Fauzi; Yaya Hasanah; Toga Simanungkalit (Jurnal Agroekoteknologi, 2016)
This research has been conducted to obtain a certain application of mulch and some plant spacing which can improve the growth of the shallot. This research had been conducted at experimental field of Faculty of Agriculture University of Sumatera Utara on October to December 2015 using a factorial randomized block design with two factor, i.e. types of mulch (no mulch, straw mulch, silver black plastic mulch) and plant spacing (20 cm x 15 cm, 20 cm x 20 cm,20 cm x 25 cm). Parameter observed were plant height, number of leaves, number of tillers, diameter of the bulbs per sample. The result showed that types of mulch significantly affect of plant height at 2 week after planting (WAP), number of leaves at 2 and 3 WAP in which types of silver black plasctic mulch showed the highest yields. Plant spacing significantly affect the parameters plant height at 3 and 4 WAP. The interaction between types of mulch and plant spacing were not significantly affect on all parameters observed.